Identification and Functional Characterization of a Tonoplast Dicarboxylate Transporter in Tomato (Solanum lycopersicum) - Liu, Ruiling; Li, Boqiang; Qin, Guozheng; Zhang, Zhanquan; Tian, Shiping (Frontiers in Plant Science, 2017)
Acidity plays an important role in flavor and overall organoleptic quality of fruit and is mainly due to the presence of organic acids. Understanding the molecular basis of organic acid metabolism is thus of primary importance for fruit quality improvement. Here, we cloned a putative tonoplast dicarboxylate transporter gene (SlTDT) from tomato, and submitted it to the NCBI database (GenBank accession number: KC733165). SlTDT protein contained 13 putative transmembrane domains in silico analysis. Confocal microscopic study using green fluorescent fusion proteins revealed that SlTDT was localized on tonoplast. The expression patterns of SlTDT in tomato were analyzed by RT-qPCR. The results indicated that SlTDT expressed in leaves, roots, flowers and fruits at different ripening stages, suggesting SlTDT may be associated with the development of different tissues. To further explore the function of SlTDT, we constructed both overexpression and RNAi vectors and obtained transgenic tomato plants by agrobacterium-mediated method. GC-MS analysis showed that overexpression of SlTDT significantly increased malate content, and reduced citrate content in tomato fruit. By contrast, repression of SlTDT in tomato reduced malate content of and increased citrate content. These results indicated that SlTDT played an important role in remobilization of malate and citrate in fruit vacuoles.